Imagining More-Than-Human Care: From Multispecies Mothering to Caring Relations in Finding the Mother Tree - Barnett, Joshua (Journal of Ecohumanism, 2023)
In the Western imaginary, care has long been pictured as a distinctly human activity—an activity undertaken primarily by women—and the paradigmatic image of caregiving has been that of a mother tending to her child. Increasingly, though, both the matricentricity and the anthropocentricity of care are being scrutinized as scholars advocate for more egalitarian and, in a few cases, more ecological conceptions of care. Examples of more-than-human care have been sparse, however, which hampers our collective capacity to imagine care beyond the human. Thus, in this essay I look for imaginative resources in forest ecologist Suzanne Simard’s (2021) New York Times bestselling book Finding the Mother Tree: Discovering the Wisdom of the Forest. This encounter reveals two connected concepts—multispecies mothering and caring relations—and opens onto an ecological ethic of care rooted in a commitment to care for caring relations, to sustain the conditions of possibility for the care that we all need to survive and flourish.